Language Use on Social Media: Reflection on Verbal Behavior and Cultural Identities of State Islamic University Undergraduates - Hetti Waluati Triana; Martin Kustati; Ike Revita; David D Peroddin; Yufni Faisol; Reflinaldi Reflinaldi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
This study aims to identify the verbal behavior characteristics of Islamic university students with the use of Facebook in order to determine the identity forms that become a representation of their language aspects. Qualitative method was applied to objectively describe the social practices, and the varying issues and objectives of linguistic features that are generated and interpreted in these discourses. The data was procured, by using content analysis and observation, from the discourses of students at State Islamic University Imam Bonjol in the form of Facebook status posts and comments written in Facebook groups. The analysis was conducted following Fairclough’s Critical Discourse Analysis with a Critical Linguistics Approach. The results showed that the language features of the students contain some characteristics that appear in the form of abbreviations or acronyms, and the insertion of elements of foreign languages mostly dominated by features of Arabic. It was also found that the status and comments of the students focused on five dominant issues: religious, university, personal, social and cultural, and national issues. It was concluded that situational, institutional, and cultural contexts influenced the students’ production of particular discourse on Facebook. Features, issues, and discourse context identified through language used by the students had become one of many ways to recognize an Islamic university student. This ability to identify a particular student is due to the language used as a medium of communication to provide space for students to create, and directly or indirectly provide extensive information about the identity of the speakers.